(untitled) (Global Journal of Science Frontier Research, 2014)
This study was carried out with the objective to assess food security situation of Mukta Kamaiyas (former agriculture bonded-labourers) and to know their strategies to cope the food deficit. Two village development committees (VDCs), namely Kohalpur in Banke and Kalika in Bardiya districts respectively were purposively selected for the study. A random household survey with semi-structured questionnaire was carried out in 120 households thus each VDC having 60 households. The questionnaire consisted of basic household sojourn and food production situation. Simultaneously, focus group discussion (FGD) and Key Informant Interview were also made during the field survey. Only 4% households were food self-sufficient whilst the larger proportions (> 75% households) had less than three months food self-sufficiency. About 36% households were unable to meet the minimum daily calorie requirement (2,144 kcal/person/day) recommended for the terai region of Nepal. The food selfinsufficiency was more severe in Kohalpur due to smaller land size, and due to rather larger family size and more dependent family members than Kalika VDC, but, food security situation was slightly better than Kalika due to the trade based entitlements (wage labour and business opportunities etc). Wage labour is the most prominent source of income for securing household’s food demand in Mukta Kamaiyas. It was further supported by the other strategies like cash loan, food borrowing, cutting of meal, less preferred food eating and so on. So, improving labour productivity through skill development and employment generation and enterprising would help to promote income generation activities and to improve food security situation as well in long term. While in short term off-season vegetable farming, poultry and small livestock husbandry would be the better options for sustaining livelihood in the rural setting of Mukta Kamaiya villages.